Apakah Tunneling Menurunkan Kinerja Perusahaan? Studi Pada Industri Manufaktur di Indonesia - Supatmi; Millenia Tri Gamasti (Politeknik Ganesha Medan, 2023)
This research aims to determine the effect of related party transactions tunneling on the manufacturing industry accounting performance and market performance. We believe that the higher the tunneling through related party transactions carried out by the company, the lower the company's performance. Related party transactions are measured by related party transactions with account receivable, other receivable and assets other than account receivables and other receivables.This research sample is 175 manufacturing industry companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020 with 525 observations as panel data. This hypothesis examined by panel data regression with Eviews program. Based on panel data regression test, this research found tunneling proxied by related party transactions with assets other than account receivables and other receivables negatively affects financial performance (ROA) means the more industry manufacturing do related party transaction with assets other than account receivables and other receivables ability to earn profit is getting lower. Also, tunneling proxied by related party transactions with assets other than account receivables and other receivables negatively affects market performance (TOBIN), the more industry manufacturing do related party transaction with assets other than account receivables and other receivables decrease ability of investment profit sharing make share price weak. This finding align with the type II agency theory that the majority shareholder dominates the minority shareholder causing agency conflict.